Glass fiber impregnating compound for SMC (Sheet Molding Compound) as well as preparation method, product and application thereof

By using glass fiber wetting agent for ultra-low hairy SMC, the problem of hairy produced in the glass fiber yarn during the cutting process is solved, the smoothness and cutting properties of the fiber are improved, and the mechanical properties of the products are improved.

CN119822651AActive Publication Date: 2025-04-15JUSHI GRP CO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510135584.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-15
Estimated Expiration
2045-02-07

AI Technical Summary

Technical Problem

The existing glass fiber yarns are prone to hairy feathers during the cutting process, resulting in reduced production efficiency and stability, and insufficient slipperiness and cutting properties.

Method used

A glass fiber wetting agent for ultra-low-haired SMC is used, which contains coupling agent, film forming agent, toughening agent, lubricant and antistatic agent, which is fixed to the surface of the glass fiber by chemical bonds to improve its clustering, toughness and stiffness.

Benefits of technology

It significantly reduces the hairy feathers produced by glass fibers during production and use, improves the smoothness and cutting properties of the fibers, and is well compatible with polyester resin, significantly improving the mechanical properties of the products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005263091280000021
    Figure BDA0005263091280000021
  • Figure BDA0005263091280000022
    Figure BDA0005263091280000022
  • Figure BDA0005263091280000061
    Figure BDA0005263091280000061
Patent Text Reader

Abstract

The invention discloses a glass fiber impregnating compound for SMC (Sheet Molding Compound). The glass fiber impregnating compound comprises effective components and water, the solid content of the impregnating compound is 3.6-12.6%; the impregnating compound comprises the following effective components in percentage by mass: 9.5 to 15.0 percent of coupling agent, 36.0 to 59.0 percent of film forming agent, 8.5 to 21.0 percent of flexibilizer, 9.0 to 20.0 percent of lubricant and 7.0 to 12.0 percent of antistatic agent, wherein the solid mass of the coupling agent accounts for 9.5 to 15.0 percent of the total solid mass of the impregnating compound; wherein the toughening agent is an organic silicon modified waterborne polyurethane emulsion; the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent, the mass ratio of the first film-forming agent to the second film-forming agent is 1: 1-1: 3.5, and the first film-forming agent is a double-crosslinking monomer modified PVAc emulsion; and the second film-forming agent is a polyester modified epoxy emulsion. Glass fiber yarns produced by coating the impregnating compound are good in surface smoothness and wear resistance, so that the fibers are not easy to generate glass fiber feathers in the production and use processes; the compatibility with polyester resin is good, the interface bonding is strong, and the mechanical property of a product can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sizing agents for glass fiber coating, and in particular to a glass fiber sizing agent for ultra-low hairiness SMC, as well as a preparation method, product and application of the sizing agent. Background Art

[0002] SMC products have many advantages such as light weight, high strength, corrosion resistance, good designability, easy molding, and easy coloring. They have been widely used in the fields of shells, chassis, bumpers and spoilers in the automotive industry, high-voltage switchgear and rectifier boxes in the electrical industry, water tank plates, waterproof plates, and bathroom facilities in the construction industry. With the continuous improvement of technology, SMC manufacturers have put forward higher requirements for production continuity, stability, and uniformity of sheets. In order to meet the needs of downstream customers, glass fiber manufacturers must develop SMC special yarns with lower hairiness. If the yarn is not wear-resistant, it is easier to produce hairiness during cutting and use. The accumulated hairiness at the knife roller will fall into the sheet in a ball, resulting in local uneven distribution of glass fiber. Customers usually need to stop the machine to clean the accumulated hairiness during use, resulting in reduced production efficiency and production stability. In addition, the smoothness and cutting properties of the yarn are also very important. Yarns with good smoothness can ensure that they can pass through plastic pipes and yarn porcelain eyes smoothly without generating a lot of hairiness; yarns with good cutting properties can ensure that the yarn is cut with one knife, avoiding the hairiness caused by repeated cutting. Summary of the invention

[0003] The present application aims to provide a glass fiber sizing for ultra-low hairiness SMC. The glass fiber produced by coating the sizing has good surface smoothness and good wear resistance, so that the fiber is not prone to glass fiber hairiness during production and use; and the sizing has good compatibility with polyester resin, strong interface bonding, and can significantly improve the mechanical properties of the product.

[0004] In order to achieve the above technical effects, this application is implemented through the following technical solutions:

[0005] According to one aspect of the present application, a glass fiber sizing for SMC is provided, the sizing comprising effective components and water; the solid content of the sizing is 3.6% to 12.6%; the effective components comprise a coupling agent, a film-forming agent, a toughening agent, a lubricant and an antistatic agent; the solid mass of each effective component of the sizing to the total solid mass of the sizing is expressed as follows:

[0006]

[0007]

[0008] Wherein, the toughening agent is a silicone-modified waterborne polyurethane emulsion;

[0009] Among them, the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent; the first film-forming agent is a double-crosslinked monomer modified PVAc emulsion; the second film-forming agent is a polyester modified epoxy emulsion; the mass ratio of the first film-forming agent to the second film-forming agent is 1:1 to 1:3.5.

[0010] The percentage of the solid mass of each effective component of the wetting agent to the total solid mass of the wetting agent is expressed as follows:

[0011]

[0012] The lubricant is a composition of oleic acid diethanolamide and tall oil diethanolamide mixed in any proportion.

[0013] Wherein, the coupling agent is a silane coupling agent containing a methacryloxy group.

[0014] Wherein, the antistatic agent is an inorganic salt containing lithium.

[0015] The organosilicon-modified waterborne polyurethane emulsion is prepared by dispersing the reaction product of toluene diisocyanate, terminal hydroxyl polydimethylsiloxane and polyisopropylene glycol in water, using dimethylol propionic acid as a chain extender.

[0016] The double cross-linked monomer modified PVAc emulsion is prepared by using diallyl phthalate as a pre-cross-linked monomer and vinyl triethoxysilane as a post-cross-linked monomer through a semi-continuous seed emulsion polymerization method.

[0017] The polyester-modified epoxy emulsion is prepared by emulsifying epoxy resin using unsaturated polyester as an emulsifier.

[0018] The epoxy resin is at least one of bisphenol A epoxy resin, bisphenol S epoxy resin and bisphenol F epoxy resin; the epoxy equivalent of the epoxy resin is 700 to 3600 g / eq.

[0019] The functions and contents of the components in the glass sizing agent for SMC in this application are as follows:

[0020] The coupling agent of the present application is a silane coupling agent (with a general structural formula of YSiX3). Among them, in the general structural formula, Y is an organic end, usually a chain olefin or a hydrocarbon group with functional groups such as amino, thiol, epoxy, azide and isocyanate at the end; X is a hydrolyzable group, such as chlorine, alkoxy, etc. Due to this special chemical structure, the silane coupling agent can be used as a bridge between the inorganic glass fiber and the organic polymer film-forming agent, so that the entire sizing agent film can be fixed to the surface of the glass fiber through chemical bonds, thereby maintaining the good bundling, toughness and stiffness of the glass fiber during processing or cutting. Preferably, the coupling agent of the present application uses a silane coupling agent containing a methacryloxy group, which can form a stable bond with the film-forming agent selected in the present application through chemical bonds, and can effectively improve the performance of the glass fiber. Exemplarily, the coupling agent of the present application can use γ-methacryloxypropyltrimethoxysilane coupling agent. At the same time, the amount of the coupling agent needs to be controlled within an appropriate range. Research has found that if the content of the coupling agent is too little, it cannot play an effective transition bridge role between the inorganic glass fiber and the organic polymer film-forming agent; if the content is too much, it will be interspersed and hinder the film-forming agent from playing its due role. Therefore, the application controls the percentage of the solid mass of the coupling agent to the total solid mass of the sizing agent to be 9.5% to 15.0%; preferably 10.0 to 14.5%; more preferably 10.5 to 14.0%.

[0021] The film-forming agent is the main component of the glass fiber sizing agent, which has the functions of protecting the glass fiber, improving the cuttability and bundling of the glass fiber and the compatibility with the matrix resin, and has a decisive influence on the continuous production and subsequent application of the glass fiber. Therefore, the selection of the film-forming agent is one of the focuses of this application. At the same time, the amount of the film-forming agent needs to be controlled within an appropriate range; if the amount of the film-forming agent is too small, the glass fiber is easily damaged by mechanical friction to produce filaments, and the compatibility with the matrix resin will be reduced; if the amount is too large, the yarn resin penetration will be slowed down, causing the impregnation problem of the yarn in the sheet. Therefore, the solid mass of the film-forming agent in this application is controlled to be 36.0-59.0% of the total solid mass of the sizing agent, preferably 40.0-57.0%, and more preferably 44.0-55.0%.

[0022] The film-forming agent used in this application is in the form of an emulsion, specifically a combination of a first film-forming agent and a second film-forming agent. Among them, the first film-forming agent is a double cross-linked monomer modified PVAc emulsion, which is based on vinyl acetate and versatate vinyl carbonate as the main monomers, diallyl phthalate (DAP) as the pre-cross-linked monomer, and vinyl triethoxysilane (VTES) as the post-cross-linked monomer, and is prepared by semi-continuous seed emulsion polymerization (reference: Synthesis and Performance Study of Double Cross-linked Monomer Modified PVAc Emulsion Adhesive [J]. Ren Jie et al. Chinese Adhesives. 2022 (31)). Compared with ordinary PVAc emulsion, the double cross-linked monomer modified PVAc emulsion has a higher degree of cross-linking, better water resistance and heat resistance after film formation, and is coated on the surface of glass fiber to make it have better bundling, and can maintain its integrity as much as possible during use to reduce hairiness. Preferably, the solid content of the double cross-linked monomer modified PVAc emulsion is 28.0% to 48.0%.

[0023] The second film-forming agent of the present application is a polyester-modified epoxy emulsion, which is formed by emulsifying epoxy resin with an unsaturated polyester containing terminal carboxyl groups as an emulsifier, and the mass ratio of unsaturated polyester to epoxy resin is controlled to be 1:4 to 1:9. After the polyester-modified epoxy emulsion is coated on the glass fiber, the epoxy component therein can ensure that the glass fiber has good bundling properties, reduce the generation of scattered fibers during the use of the glass fiber, and then accumulate into hairiness; at the same time, it has good compatibility with the target reinforcement matrix-unsaturated resin, and can effectively improve the mechanical properties of glass fiber composite products. Preferably, the epoxy resin is at least one of bisphenol A epoxy resin, bisphenol S epoxy resin and bisphenol F epoxy resin; further preferably, the epoxy equivalent of the epoxy resin is 700 to 3600 g / eq.

[0024] In addition, the present application needs to control the dosage relationship between the first film-forming agent and the second film-forming agent. The study found that when the mass ratio of the first film-forming agent to the second film-forming agent is controlled to be 1:1 to 1:3.5, the yarn has better bundling, less hairiness, higher stiffness, better compatibility with unsaturated resins, and higher mechanical strength of the product. When the proportion of the first film-forming agent is too high, it is easy to cause the resin penetration of the glass fiber product to slow down and the mechanical properties of the product to decrease; when the proportion of the second film-forming agent is too high, it is easy to cause the brittleness of the glass fiber product to increase, the film is easily destroyed, and the stiffness decreases significantly during use. Preferably, the mass ratio of the first film-forming agent to the second film-forming agent is 1:1.2 to 1:3.4; more preferably, it is 1:1.4 to 1:3.2.

[0025] Toughening agent refers to a substance that can increase the flexibility of the film layer of the film-forming agent. Thermosetting resin emulsion film-forming agents, such as epoxy emulsions and PVAc emulsions, are relatively brittle after film curing. When the glass fiber is bonded to a part subjected to external force, cracks are easily generated and rapidly expand, resulting in cracking of the film layer, thereby generating a large number of glass fiber hairs and loose threads. Therefore, the present application adopts a toughening agent to reduce the brittleness of the film layer, increase the toughness, and improve the strength of the glass fiber film layer to resist external forces, thereby reducing the hairiness generated by the glass fiber during use. Preferably, the toughening agent is selected from a water-based polyurethane emulsion modified with silicone, which is formed by dispersing the reaction product of toluene diisocyanate, terminal hydroxyl polydimethylsiloxane and polyisopropylene glycol in water with dimethylol propionic acid as a chain extender (reference: Preparation and performance study of high-content water-based polyurethane emulsion modified with silicone [J]. Huang Qin et al. Coating Industry. 2006 (9)).

[0026] At the same time, the amount of toughening agent should also be controlled within an appropriate range. Too much toughening agent will destroy the film-forming agent system, while too little toughening agent will cause excessive hairiness of the glass fiber. Therefore, the solid mass of the toughening agent is controlled to be 8.5-21.0% of the total solid mass of the sizing agent, preferably 11.0-18.0%, and more preferably 12.5-15.5%.

[0027] In the present application, the lubricant is mainly used to ensure the lubrication effect of the glass fiber in processes such as wire drawing, winding and SMC process production. Preferably, the lubricant is a composition formed by mixing oleic acid diethanolamide and tall oil diethanolamide in any proportion. At the same time, the amount of lubricant must also be controlled within an appropriate range. Too little content will not achieve the lubricating effect, and too much content will cause the surface of the glass fiber to become sticky and stranded, affecting the cutting dispersion of the glass fiber and having a negative impact on the mechanical properties of the glass fiber composite material. Therefore, the present application controls the solid mass of the lubricant to account for 9.0 to 20.0% of the total solid mass of the impregnating agent, preferably 10.5 to 19.5%, and more preferably 12.0 to 19.0%.

[0028] Since glass fiber is very easy to generate static electricity during the cutting process, causing the problem of uneven dispersion, the present application uses an antistatic agent to improve the antistatic performance of glass fiber. Preferably, the antistatic agent is selected from an inorganic salt containing lithium, and more preferably lithium nitrate. At the same time, the amount of the antistatic agent must also be controlled within an appropriate range. Too much will cause the film-forming agent system to be destroyed, and too little will cause static electricity problems in the glass fiber. Therefore, the present application controls the solid mass of the antistatic agent to account for 7.0 to 12.0% of the total solid mass of the impregnant, preferably 7.5 to 11.5%, and more preferably 8.0 to 11.0%.

[0029] The water in the present application is the dispersed phase of each component in the wetting agent. Wherein, the water is preferably deionized water.

[0030] According to a second aspect of the present application, a method for preparing the aforementioned glass fiber sizing agent for SMC is provided, comprising the following steps:

[0031] S1: Pre-dispersing the coupling agent into water 10 to 50 times its volume to prepare a coupling agent solution;

[0032] S2: adding the lubricant and the antistatic agent to water 10 to 40 times their volumes for pre-dissolution, respectively, to prepare a lubricant solution and an antistatic agent solution, respectively, then mixing the two solutions evenly, and adding them to the solution obtained in step S1;

[0033] S3: diluting the first film-forming agent with water 5 to 11 times its volume; diluting the second film-forming agent with water 4 to 10 times its volume, and then sequentially adding the two into the solution obtained in step S2, mixing and stirring evenly;

[0034] S4: Add the toughening agent into water 5 to 15 times its volume for pre-dissolution, then add it into the solution obtained in step S3, mix and stir evenly.

[0035] According to a third aspect of the present application, a glass fiber product produced by coating the SMC with a glass fiber sizing agent is provided.

[0036] According to a fourth aspect of the present application, application of the glass fiber product in the automotive and construction fields is provided.

[0037] The glass fiber reinforced resin matrix produced by coating the SMC with a glass fiber sizing agent is an unsaturated polyester resin.

[0038] The glass fiber yarn produced by coating the sizing agent described in the present application has good surface smoothness and good wear resistance, so that the fiber is not prone to glass fiber hairiness during production and use; and has good compatibility with polyester resin and strong interface bonding, which can significantly improve the mechanical properties of the product. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other arbitrarily. The following is an example of the preferred value range of each component included in the glass fiber composition of the present application.

[0040] Preferred Example 1

[0041] The glass fiber sizing agent for SMC according to the present application comprises effective components and water, wherein the solid content of the sizing agent is 3.6% to 12.6%; the effective components comprise a coupling agent, a film-forming agent, a toughening agent, a lubricant and an antistatic agent; the percentage of the solid mass of each effective component of the sizing agent to the total solid mass of the sizing agent is expressed as follows:

[0042]

[0043] Wherein, the toughening agent is a silicone-modified waterborne polyurethane emulsion;

[0044] Among them, the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent; the first film-forming agent is a double-crosslinked monomer modified PVAc emulsion; the second film-forming agent is a polyester modified epoxy emulsion; the mass ratio of the first film-forming agent to the second film-forming agent is 1:1 to 1:3.5.

[0045] Preferred Example 2

[0046] The glass fiber sizing agent for SMC according to the present application comprises effective components and water, and the solid content of the sizing agent is 4.1-12.1%; wherein the solid mass of each component of the effective component accounts for the percentage of the total solid mass of the sizing agent as follows:

[0047]

[0048]

[0049] Wherein, the toughening agent is a silicone-modified waterborne polyurethane emulsion;

[0050] Among them, the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent; the first film-forming agent is a double-crosslinked monomer modified PVAc emulsion; the second film-forming agent is a polyester modified epoxy emulsion; the mass ratio of the first film-forming agent to the second film-forming agent is 1:1.2 to 1:3.4.

[0051] Preferred Example 3

[0052] The glass fiber sizing agent for SMC according to the present application comprises effective components and water, and the solid content of the sizing agent is 4.1-12.1%; wherein the solid mass of each component of the effective component accounts for the percentage of the total solid mass of the sizing agent as follows:

[0053]

[0054] Wherein, the toughening agent is a silicone-modified waterborne polyurethane emulsion;

[0055] Among them, the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent; the first film-forming agent is a double-crosslinked monomer modified PVAc emulsion; the second film-forming agent is a polyester modified epoxy emulsion; the mass ratio of the first film-forming agent to the second film-forming agent is 1:1.2 to 1:3.4.

[0056] The lubricant is a composition of oleic acid diethanolamide and tall oil diethanolamide mixed in any proportion.

[0057] Preferred Example 4

[0058] The glass fiber sizing agent for SMC according to the present application comprises effective components and water, and the solid content of the sizing agent is 4.1-12.1%; wherein the solid mass of each component of the effective component accounts for the percentage of the total solid mass of the sizing agent as follows:

[0059]

[0060]

[0061] Wherein, the toughening agent is a silicone-modified waterborne polyurethane emulsion;

[0062] Among them, the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent; the first film-forming agent is a double-crosslinked monomer modified PVAc emulsion; the second film-forming agent is a polyester modified epoxy emulsion; the mass ratio of the first film-forming agent to the second film-forming agent is 1:1.2 to 1:3.4.

[0063] The lubricant is a composition of oleic acid diethanolamide and tall oil diethanolamide mixed in any proportion.

[0064] The coupling agent is a silane coupling agent containing a methacryloxy group.

[0065] Preferred Example 5

[0066] The glass fiber sizing agent for SMC according to the present application comprises effective components and water, and the solid content of the sizing agent is 4.6-11.6%; wherein the solid mass of each component of the effective component accounts for the percentage of the total solid mass of the sizing agent as follows:

[0067]

[0068] Wherein, the toughening agent is a silicone-modified waterborne polyurethane emulsion;

[0069] Among them, the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent; the first film-forming agent is a double-crosslinked monomer modified PVAc emulsion; the second film-forming agent is a polyester modified epoxy emulsion; the mass ratio of the first film-forming agent to the second film-forming agent is 1:1.4 to 1:3.2.

[0070] Preferred Example 6

[0071] The glass fiber sizing agent for SMC according to the present application comprises effective components and water, and the solid content of the sizing agent is 4.6-11.6%; wherein the solid mass of each component of the effective component accounts for the percentage of the total solid mass of the sizing agent as follows:

[0072]

[0073] Wherein, the toughening agent is a silicone-modified waterborne polyurethane emulsion;

[0074] Among them, the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent; the first film-forming agent is a double-crosslinked monomer modified PVAc emulsion; the second film-forming agent is a polyester modified epoxy emulsion; the mass ratio of the first film-forming agent to the second film-forming agent is 1:1.4 to 1:3.2.

[0075] Wherein, the antistatic agent is an inorganic salt containing lithium.

[0076] The organosilicon-modified waterborne polyurethane emulsion is prepared by dispersing the reaction product of toluene diisocyanate, terminal hydroxyl polydimethylsiloxane and polyisopropylene glycol in water, using dimethylol propionic acid as a chain extender.

[0077] Preferred Example 7

[0078] The glass fiber sizing agent for SMC according to the present application comprises effective components and water, and the solid content of the sizing agent is 4.6-11.6%; wherein the solid mass of each component of the effective component accounts for the percentage of the total solid mass of the sizing agent as follows:

[0079]

[0080] Wherein, the toughening agent is a silicone-modified waterborne polyurethane emulsion;

[0081] Among them, the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent; the first film-forming agent is a double-crosslinked monomer modified PVAc emulsion; the second film-forming agent is a polyester modified epoxy emulsion; the mass ratio of the first film-forming agent to the second film-forming agent is 1:1.4 to 1:3.2.

[0082] Wherein, the antistatic agent is an inorganic salt containing lithium.

[0083] The organosilicon-modified waterborne polyurethane emulsion is prepared by dispersing the reaction product of toluene diisocyanate, terminal hydroxyl polydimethylsiloxane and polyisopropylene glycol in water, using dimethylol propionic acid as a chain extender.

[0084] The double cross-linked monomer modified PVAc emulsion is prepared by using diallyl phthalate as a pre-cross-linked monomer and vinyl triethoxysilane as a post-cross-linked monomer through a semi-continuous seed emulsion polymerization method.

[0085] Preferred Example 8

[0086] The glass fiber sizing agent for ultra-low hairiness SMC according to the present application comprises effective components and water, and the solid content of the sizing agent is 4.6-11.6%; wherein the solid mass of each component of the effective component accounts for the percentage of the total solid mass of the sizing agent as follows:

[0087]

[0088] Wherein, the toughening agent is a silicone-modified waterborne polyurethane emulsion;

[0089] Among them, the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent; the first film-forming agent is a double-crosslinked monomer modified PVAc emulsion; the second film-forming agent is a polyester modified epoxy emulsion; the mass ratio of the first film-forming agent to the second film-forming agent is 1:1.4 to 1:3.2.

[0090] Wherein, the antistatic agent is an inorganic salt containing lithium.

[0091] The organosilicon-modified waterborne polyurethane emulsion is prepared by dispersing the reaction product of toluene diisocyanate, terminal hydroxyl polydimethylsiloxane and polyisopropylene glycol in water, using dimethylol propionic acid as a chain extender.

[0092] The double cross-linked monomer modified PVAc emulsion is prepared by using diallyl phthalate as a pre-cross-linked monomer and vinyl triethoxysilane as a post-cross-linked monomer through a semi-continuous seed emulsion polymerization method.

[0093] The polyester-modified epoxy emulsion is prepared by emulsifying epoxy resin with unsaturated polyester as emulsifier; the epoxy resin is at least one of bisphenol A epoxy resin, bisphenol S epoxy resin and bisphenol F epoxy resin; the epoxy equivalent of the epoxy resin is 700 to 3600 g / eq.

[0094] The beneficial effects of selecting the above content ranges of each component in the glass fiber sizing for SMC of the present application will be described by providing specific experimental data through examples. Some specific examples of the glass fiber sizing for SMC of the present application are listed below.

[0095] Example

[0096] The percentage of the solid mass of each component in the embodiment of the glass fiber sizing for SMC of the present application to the total solid mass is shown in Table 1.

[0097] Table 1 Example formula of glass fiber sizing agent for SMC

[0098]

[0099] Table 1 (Continued) Example formula of glass fiber sizing agent for SMC

[0100]

[0101]

[0102] The preparation methods of Examples 1 to 12 are as follows:

[0103] S1: Pre-disperse the coupling agent by adding water 10 to 50 times its volume to prepare a coupling agent solution;

[0104] S2: adding the lubricant and the antistatic agent to water 10 to 40 times their volumes to pre-dissolve them, respectively, to prepare a lubricant solution and an antistatic agent solution, respectively, and then mixing the two solutions evenly and adding them to the solution obtained in step S1;

[0105] S3: diluting the first film-forming agent with water 5 to 11 times its volume; diluting the second film-forming agent with water 4 to 10 times its volume, and then sequentially adding the two into the solution obtained in step S2, mixing and stirring evenly;

[0106] S4: Add the toughening agent into water 5 to 15 times its volume for pre-dissolution, then add it into the solution obtained in step S3, mix and stir evenly.

[0107] In order to further illustrate the beneficial effects of the present application, two commonly used glass fiber sizing agents (Comparative Example 1 and Comparative Example 2) are selected. The percentage of the solid content of each effective component in the comparative example to the total solid content of the sizing agent is expressed as follows, and the balance is water:

[0108] Comparative Example 1

[0109]

[0110] Comparative Example 2

[0111]

[0112] Comparative Example 3

[0113]

[0114]

[0115] Table 2 shows the performance test results of glass fiber plied yarn products produced by using the sizing agents of Examples 1 to 12 and Comparative Examples 1 to 2. To ensure the comparability of the test results, the combustible content of the glass fiber prepared in each Example and Comparative Example has been ensured to be substantially the same (control range 1.3 to 1.6, center value 1.45) during the sample preparation process, that is, the percentage of the solid mass of the sizing agent applied on the surface of the glass fiber to the mass of the glass fiber in the Examples and Comparative Examples is substantially the same. In addition, it has been ensured that the other raw materials and production process parameters used in the mechanical property test of the glass fiber prepared in each Example and Comparative Example are consistent, so as to compare the performance of the glass fiber in parallel.

[0116] Table 2 Glass fiber performance test results

[0117]

[0118]

[0119] Table 2 (Continued) Glass fiber performance test results

[0120]

[0121] Note:

[0122] Among them, the glass fiber reinforced unsaturated polyester resin sample used for mechanical properties (including bending strength and lateral compression strength) testing is prepared by SMC (sheet molding compound) molding.

[0123] From the test results of the above embodiments, we can see that the test results of the fluff amount of the glass fiber coated with the wetting agent of the present application have obvious advantages over the comparative example, and the mechanical properties of the prepared fiber-reinforced unsaturated polyester resin are also significantly better than those of the comparative example, such as the glass fiber prepared by the wetting agent of Examples 6 and 7, which performs particularly well; in addition, it also has the advantages of high stiffness and good surface smoothness.

[0124] It can be seen that the glass fiber sizing agent formula and process provided in this application are scientific and reasonable, the glass fiber coated with the sizing agent has better compatibility with the unsaturated polyester resin, can form a stronger interface bonding, and the surface performance of the product is also improved.

[0125] The contents described above may be implemented individually or in combination in various ways, and these variations are all within the protection scope of this application.

[0126] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A glass fiber sizing agent for SMC, characterized in that: The wetting agent comprises effective components and water; the solid content of the wetting agent is 3.6% to 12.6%; the effective components comprise coupling agents, film formers, toughening agents, lubricants and antistatic agents; the percentage of the solid mass of each effective component of the wetting agent to the total solid mass of the wetting agent is expressed as follows: Wherein, the toughening agent is a silicone-modified waterborne polyurethane emulsion; Among them, the film-forming agent is a mixture of a first film-forming agent and a second film-forming agent; the first film-forming agent is a double-crosslinked monomer modified PVAc emulsion; the second film-forming agent is a polyester modified epoxy emulsion; the mass ratio of the first film-forming agent to the second film-forming agent is 1:1 to 1:3.

5.

2. The glass fiber sizing agent for SMC according to claim 1, characterized in that: The percentage of the solid mass of each effective component of the infiltrant to the total solid mass of the infiltrant is expressed as follows:

3. The glass fiber sizing agent for SMC according to claim 1 or 2, characterized in that: The lubricant is a composition formed by mixing oleic acid diethanolamide and tall oil diethanolamide in any proportion.

4. The glass fiber sizing agent for SMC according to claim 1 or 2, characterized in that: The coupling agent is a silane coupling agent containing a methacryloxy group; and the antistatic agent is an inorganic salt containing lithium.

5. The glass fiber sizing agent for SMC according to claim 1 or 2, characterized in that: The organosilicon-modified waterborne polyurethane emulsion is prepared by using dimethylol propionic acid as a chain extender and by dispersing the reaction product of toluene diisocyanate, terminal hydroxyl polydimethylsiloxane and polyisopropylene glycol in water.

6. The glass fiber sizing agent for SMC according to claim 1 or 2, characterized in that: The double cross-linking monomer modified PVAc emulsion is prepared by using diallyl phthalate as a pre-cross-linking monomer and vinyl triethoxysilane as a post-cross-linking monomer through a semi-continuous seed emulsion polymerization method.

7. The glass fiber sizing agent for SMC according to claim 1 or 2, characterized in that: The polyester modified epoxy emulsion is prepared by emulsifying epoxy resin using unsaturated polyester as an emulsifier; the epoxy resin is at least one of bisphenol A epoxy resin, bisphenol S epoxy resin and bisphenol F epoxy resin; the epoxy equivalent of the epoxy resin is 700 to 3600 g / eq.

8. A method for preparing a glass fiber sizing for SMC according to any one of claims 1 to 7, characterized in that: The steps include: S1: Pre-dispersing the coupling agent into water 10 to 50 times its volume to prepare a coupling agent solution; S2: adding the lubricant and the antistatic agent to water 10 to 40 times their volumes for pre-dissolution, respectively, to prepare a lubricant solution and an antistatic agent solution, respectively, then mixing the two solutions evenly, and adding them to the solution obtained in step S1; S3: diluting the first film-forming agent with water 5 to 11 times its volume; diluting the second film-forming agent with water 4 to 10 times its volume, and then sequentially adding the two into the solution obtained in step S2, mixing and stirring evenly; S4: Add the toughening agent into water 5 to 15 times its volume for pre-dissolution, then add it into the solution obtained in step S3, mix and stir evenly.

9. A glass fiber product produced by coating the glass fiber sizing for SMC as claimed in any one of claims 1 to 7.

10. Use of the glass fiber product according to claim 9 in the fields of automobiles and construction.

Citation Information

Patent Citations

  • Glass fiber impregnating compound high in permeating speed and application thereof in producing twistless roving

    CN105819709A

  • Structure-enhanced SMC (Sheet Moulding Compound) glass fibre impregnating agent and application thereof in production of twistless roving

    CN108996922A

  • Low-odor glass fiber impregnating compound, and preparation method and application thereof

    CN111499221A

  • Glass fiber impregnating compound for high-penetrability SMC (Sheet Molding Compound) as well as preparation method and application of glass fiber impregnating compound

    CN113213779A

  • Epoxy sizing composition for filament winding

    US20050279140A1